2014
DOI: 10.1097/aog.0000000000000411
|View full text |Cite
|
Sign up to set email alerts
|

Association of Venous Thromboembolism With Hormonal Contraception and Thrombophilic Genotypes

Abstract: II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
62
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(66 citation statements)
references
References 30 publications
2
62
0
2
Order By: Relevance
“…The use of low‐dose COCs containing cyproterone (nine studies, Fig. ), desogestrel (16 studies, Fig. ), drospirenone (10 studies,Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of low‐dose COCs containing cyproterone (nine studies, Fig. ), desogestrel (16 studies, Fig. ), drospirenone (10 studies,Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Also excluded were articles that only reported the risk of VTE among a mixed group of COC users with different progestogen‐containing COCs (e.g., “third generation”), and articles where the reference group cited the use of COC with non‐specified progestogens . Five of the included studies did not clearly state the estrogen dose contained; one study spanning 1991 through 1995 relied on the UK Mediplus database, where the majority of recorded prescriptions were for low‐dose COC formulations, and the other four studies were conducted after 2000, when pills containing 50 μg ethinyl estradiol or more were uncommonly prescribed.…”
Section: Methodsmentioning
confidence: 99%
“…One of them suggested that the odds of VTE are higher among smokers using high-dose of progestin compared with smokers who did not use this hormonal treatment (27). Another study showed significantly elevated odds of VTE among women with factor V Leiden who used MPA comparing with non-use (28). Christiansen et al noted an elevated chance of recurrent VTE among women with a history of VTE using high-doses of progestin but that did not reach statistical significance (29).…”
Section: Discussionmentioning
confidence: 99%
“…Two studies (one cohort105 and one case-control250 study) did not find a statistically significant difference between CVR and EE/LNG COC users. The third (cohort) study245 reported an increased risk of VTE (RR 1.9; 95% CI 1.3–2.7) in women using the CVR compared to EE/LNG COC users.…”
Section: Health Risks Associated With Chc Usementioning
confidence: 89%